2020
DOI: 10.5152/tjg.2020.19058
|View full text |Cite
|
Sign up to set email alerts
|

Does periampullary diverticulum affect ERCP cannulation and post-procedure complications? an up-to-date meta-analysis

Abstract: Stem cells for pancreatitis 425 Gastric injury and bacterial overgrowth 433 The effect of visceral fat on SMA configuration 451 Antiplatelet agents in ulcerative colitis 459 Differentiation of BMSCs into intestinal ce 466 GERDOFF ® efficacy in patients with GERD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
0
13
0
2
Order By: Relevance
“…Song et al [ 31 ] reported that recurrent bile duct stones were more likely to be brown pigmented stones than cholesterol-based stones. This may be because pigment-based stones are often related to bacterial infection, and the formation of biliary sludge will contribute to recurrent stone formation over time[ 32 - 34 ]. The brown pigmented stones that form as a result of bacterial infection are soft and easy to fragment and generate abundant debris.…”
Section: Discussionmentioning
confidence: 99%
“…Song et al [ 31 ] reported that recurrent bile duct stones were more likely to be brown pigmented stones than cholesterol-based stones. This may be because pigment-based stones are often related to bacterial infection, and the formation of biliary sludge will contribute to recurrent stone formation over time[ 32 - 34 ]. The brown pigmented stones that form as a result of bacterial infection are soft and easy to fragment and generate abundant debris.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of our patients with perforation were compatible with the risk factors in the literature, but a statistical analysis could not be performed due to the low number of patients. 13,14,45 This study was conducted in a center with a high number of ERCP performed every year. In addition, our institution is a tertiary center where complex cases are referred to.…”
Section: Discussionmentioning
confidence: 99%
“…4 In addition, precut sphincterotomy, intramural contrast injection, and the presence of periampullary diverticulum (PAD) were associated with post-ERCP perforation. 13,14 Analyzing the factors that predict AEs developing after ERCP may be very important in reducing procedure-associated morbidity and mortality by defining patients that would be at high risk. The number of studies in which all complications are evaluated and risk factors are analyzed in the same patient group is few.…”
mentioning
confidence: 99%
“…ERCP işlemine bağlı erken komplikasyon sıklığı açısından gruplar benzerdi (PAD olmayan grupta n=21, %3.1, PAD (12). PAD hastalarında kanülasyon başarısındaki zaman içerisinde gözlenen bu artış yeni geliştirilen cihazların sağladığı teknik avantajlar ile birlikte gelişen manipülasyon teknikleri ve ERCP konusunda deneyim artışı ile ilişkili olarak değerlendirilebilir.…”
Section: Gereç Ve Yöntemunclassified
“…ERCP esnasında PAD olan hastalarda PAD olmayan hastalara göre kanülasyon oranı ve komplikasyon riski konusunda literatürde az sayıda çalışma mevcut olup veriler çelişkilidir. Eski tarihli çalışmalar çoğunlukla PAD'lerin ERCP esnasında kanülasyon zorluğu oluşturduğunu ve komplikasyon riskini artırdığını gösterirken (6-8), son zamanlarda yapılan bazı çalışmalar ise ek kanülasyon tekniklerine daha çok ihtiyaç duyulmakla birlikte kanülasyon oranı ve komplikasyon sıklığının benzer olduğunu raporlamıştır (9)(10)(11)(12). Ayrıca papillanın divertiküle göre yönünün de kanülasyon başarısını etkilediği gösterilmiştir (10).…”
Section: Introductionunclassified